The effects of social isolation on cognition : social loneliness reduces cognitive performance in older adults : a thesis presented in partial fulfilment of the requirement for the degree of Master of Science in Psychology at Massey University, Palmerston North, New Zealand - Whitehouse, Catherine (Massey University, 2013)
The present cross-sectional study examined the influence of social isolation on cognitive performance among older adults aged 65-84 years old. This study extended previous work on social isolation and cognition in two ways. While previous research has found a link between social isolation and cognition, few have examined the relationship between different forms of social isolation and different domains of cognition simultaneously. Secondly, a link between social loneliness and cognition has not been examined. Therefore, the current study examined the impact of four different types of social isolation (social loneliness, emotional loneliness, perceived social support and objective social isolation) on global cognition and cognitive domains (memory, fluency, language and visuospatial ability). The cross-sectional data from the New Zealand Longitudinal Study of Ageing (NZLSA) (2010) was used for analysis. The NZLSA study included questions about demographic information, mental and physical well-being, loneliness, social support, social networks and cognition. Using multiple regression analyses the influence of social isolation on cognitive functions was investigated. Results showed that various forms of social isolation may be differentially important for cognitive performance in the older adult, with social loneliness the only measure of social isolation that influences cognition. The results also suggested that if a form of social isolation affects cognition, the different cognitive domains such as global cognition, fluency, language and visuospatial ability respond in a similar pattern. Explanations of why social loneliness influences cognition is discussed. Limitations of the study and implications for future research, such as the need for a longitudinal study that simultaneously assesses the links between the various forms of social isolation and cognition, is also discussed.
Keywords: Social isolation; Loneliness in old age; Cognition in old age; Social isolation and cognition